2021
DOI: 10.1364/josab.433804
|View full text |Cite
|
Sign up to set email alerts
|

Design of a passively mode-locking whispering-gallery-mode microlaser

Abstract: Ultrahigh-repetition-rate lasers will become vital light sources for many future technologies; however, their realization is challenging because the cavity size must be minimized. Whispering-gallery-mode (WGM) microresonators are attractive for this purpose since they allow the strong light–matter interaction usually needed to enable mode locking. However, the optimum parameter ranges are entirely unknown since no experiments have yet been conducted. Here, we numerically investigate pulsed operation in a toroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The dissipation rate of cavity mode can be effectively controlled by using gain competition, and the resonance evolution of the probe signal can be controlled while the pump remains unchanged [80]. Furthermore, recent studies have shown the parameter design of passively modelocking (ML) gain lasers [81]. It is found that the threshold of passively mode-locking is related to the gain and dispersion.…”
Section: Other Nonlinear Effects and Applicationsmentioning
confidence: 99%
“…The dissipation rate of cavity mode can be effectively controlled by using gain competition, and the resonance evolution of the probe signal can be controlled while the pump remains unchanged [80]. Furthermore, recent studies have shown the parameter design of passively modelocking (ML) gain lasers [81]. It is found that the threshold of passively mode-locking is related to the gain and dispersion.…”
Section: Other Nonlinear Effects and Applicationsmentioning
confidence: 99%
“…The realization of a mode-locked laser based on the introduction of saturable absorber into chip-based laser has been confirmed on the silicon nitride integrated platform, 138 , 162 which can also provide a reference for the research of mode-locked lasers on an LNOI active light source platform. In addition, the multilongitudinal mode laser output based on REI-doped LNOI microcavity is also expected to achieve a mode-locked laser by introducing a saturable absorber or loading active regulation, such as electro-optic modulation to lock each longitudinal mode signal 163 . In the early stage, the application of the electro-optic effect of LN to realize mode-locked lasers was demonstrated on the erbium-doped LN weak waveguide 164 …”
Section: Application Prospects Of Lnoi-based Lasers and Amplifiersmentioning
confidence: 99%
“…In addition, the multilongitudinal mode laser output based on REI-doped LNOI microcavity is also expected to achieve a mode-locked laser by introducing a saturable absorber or loading active regulation, such as electro-optic modulation to lock each longitudinal mode signal. 163 In the early stage, the application of the electro-optic effect of LN to realize mode-locked lasers was demonstrated on the erbium-doped LN weak waveguide. 164…”
Section: Chip-based Microcombsmentioning
confidence: 99%